Eco‐Efficient Ultrasonic‐Responsive Synthesis of Primary O‐Alkyl and O‐Aryl Thiocarbamates Using Brønsted Acid Ionic Liquid [H‐NMP][HSO4] in Aqueous Media at Room Temperature. Issue 15 (18th April 2018) - Inaloo, Iman Dindarloo; Majnooni, Sahar
Abstract: In the present report, a highly efficient, simple and one‐pot process has been reported for the preparation of novel series of primary O ‐alkyl and O ‐aryl thiocarbamates through the reaction of aliphatic alcohols and phenols with thiocyanate salts in the present of N ‐methyl‐2‐pyrrolidonium hydrogen sulfate [H‐NMP][HSO4 ] as a reusable promoter. This process has also been done in aqueous media at room temperature under ultrasound irradiation. All reactions preceded smoothly and the titled products were obtained in good to excellent yields. Abstract : An improved method for the synthesis of primary O‐alkyl and O‐aryl thiocarbamates derivatives is described using aliphatic alcohols or phenols and thiocyanate salts in aqueous media at room temperature under ultrasound irradiation. Presented approach provides several advantages such as good functional group tolerance, short reaction time, simple work‐up procedure, higher yield, waste‐free and without needs any transition metals as the catalyst or toxic substances.